If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10y = 2x + -6 Reorder the terms: 10y = -6 + 2x Solving 10y = -6 + 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '10'. y = -0.6 + 0.2x Simplifying y = -0.6 + 0.2x
| y(-1)=3(-1)+3 | | 4(9x+5)=11(7x-6) | | d-12=7 | | -8=9+n | | (3x-6)(x-7)=0 | | 16=f-2 | | 615=551+32j | | -7=3+g | | 8=6+z | | 9x+40=4x+15 | | x-9=-9 | | y+3=-4 | | 2[x+7]-34=4x-11x+4[x-1] | | w-4=-3 | | 42j+19-19j=-28 | | -13.6+x=-6.2 | | 4(5x+4)=10(-3x+6) | | 17y+13y+2y+-19=-13 | | 39.99+.4m=55.99 | | (3x-6)(x-7)= | | 15+x=-7 | | 39.99+4m=59.99 | | .015w-1.85=1.615 | | x^2-22=5 | | 7x+14=4x-2 | | -4+9=13x-2-12x | | 3x+86=8x-9 | | 14+6a-8=28 | | -4x^2+10x+6=0 | | (x+7)(x-7)=32 | | 8x-11=-3x-4 | | 5(X-1)=10-2(3X+2) |